Susceptibility of the dengue vector, Aedes aegypti on the larvicidal and repellent activity of rhizome plant extracts - Sayono, Sayono; Risyandi Anwar; Othman Wan Norafikah (Penerbit Universiti Kebangsaan Malaysia, 2024)
The insecticidal potential of several plant secondary metabolites provides new hope for dengue vector control in endemic areas. This study evaluated the susceptibility of Aedes aegypti mosquitoes to the larvicidal and repellent activity of rhizome plant extracts. Sixteen extract types of Kaempferia galanga, Alpinia galanga, Zingiber zerumbet, and Curcuma aeruginosa resulted from a maceration extraction based on methanol, ethyl acetate, n-hexane, and butanol solvents were occupied. The temephos-susceptible third-instar-larvae of Ae. aegypti were subjected to larvicidal bioassay. Concentration levels of 50, 100, 250, 500, and 1,000 ppm were used in the initial bioassay test five times replicated where each replicate consisting of 20 larvae. Larval mortality was calculated in 24h and 48h post-exposure. A total of 50 laboratory strain Ae. aegypti aged 3-5 days were placed in a chamber. Repellent cream was applied to the right arm while the left arm served as a control. The arms were inserted into the chamber and the number of mosquitoes perched within 30 minutes were counted. Post-exposure of 50% and 90% lethal exposure (LC50-LC90) and 50% and 90% effective concentration (EC50-EC90) were determined. Within 24 hours, seven extract types indicated effective larvicidal concentrations, namely n-hexane extracts of K. galanga, A. galanga, Z. zerumbet, C. aeruginosa with the LC50 of 18.693, 41.926, 109.247, and 205.500 ppm; methanol of C. aeruginosa (179.291 ppm); and ethyl acetate of A. galanga (306.200 ppm). Six extract types showed the lowest concentrations of repellents, namely ethyl acetate and methanol of A. galanga (1.558% and 2.629%); methanol, ethyl-acetate, and n-hexane of Z. zerumbet (2.525, 3.946 and 4.481%); and n-hexane of K. galanga (4.338%). Aedes aegypti larvae were susceptible to the hexane extract of four rhizome plants while the adults were susceptible to Z. zerumbet and K. galanga extracts. Of these, the hexane extract of the K. galanga affect most or kills/repell more both adult and larvae of Aedes. The stability of extracts, the practical formulation of larvicides and repellents; and the isolation of chemical compounds are important to be investigated in the future.